A novel linear framework for Phasor Measurement Unit placement considering the effect of adjacent zero-injection buses. (February 2019) - Razavi, Seyed-Ehsan; Falaghi, Hamid; Singh, Chanan; Aghaei, Jamshid; Nezhad, Ali Esmaeel
Graphical abstract: Highlights: A Linear PMU placement approach is proposed. The topological observability of the network has been considered. The model is developed to include single contingencies both on the lines and PMUs. The measurement redundancy among the set of solutions is maximized. Abstract: A novel linear approach for Phasor Measurement Units (PMUs) placement is proposed in this paper to ensure the topological observability taking into consideration the impacts caused by the adjacent zero-injection buses (ZIBs). The observability analysis in the paper is performed utilizing merely the main topological observability rules. Furthermore, the model is developed to include all possible single contingencies both on the lines and PMUs even where adjacent ZIBs are highly interconnected. To this end, the common approach for handling contingencies is enhanced. Moreover, the presented framework incorporates a subsidiary objective, i.e. maximizing the measurement redundancy among the set of solutions with the minimum number of PMUs beside the main objective, i.e. minimizing the number of the required PMUs. In this regard, a unified Integer Linear Programming (ILP) is used to solve the proposed optimisation problem. It is worth noting that the suggested approach is applied to different test systems like IEEE 14-bus, 30-bus, 39-bus, 57-bus as well as 118-bus system to validate the effectiveness and efficiency of the proposed framework and the obtained results are compared to those reported by the prior researches.